2020
DOI: 10.1080/13676261.2020.1772464
|View full text |Cite
|
Sign up to set email alerts
|

Friendship barriers and supports: thoughts of young people with intellectual disabilities

Abstract: Friendship barriers and supports: Thoughts of young people with intellectual disabilitiesA great deal of research has been undertaken during the last few decades regarding the life experiences of young people with intellectual disabilities (ID). However, not much has specifically focused on the friendships of people with ID. This article aims to present the friendship experiences of young people with ID who are in their transition process to adult life. It focuses on their reflections on their own friendships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Sin embargo, es necesario investigar esta metodología para poderla valorar apropiadamente (García-Iriarte et al, 2017). Mayor consenso existe en la necesidad de que los profesionales de apoyo desarrollen acciones específicas relacionadas con la creación y/o mantenimiento de las redes de relaciones personales, en concreto identificar fuentes de apoyo y diseñar estrategias que permitan a las personas con discapacidad ampliar su red natural de apoyo (García-Iriarte et al, 2016), así como propiciar encuentros que supongan un reconocimiento y valorización de la persona y puedan sentar las bases para otras relaciones más estrechas (Bigby y Wiesel, 2015;Diaz-Garolera et al, 2020). Brophy et al (2015) plantean que se deben desarrollar apoyos creativos e innovadores en coordinación con otros recursos formales e informales de la comunidad, de acuerdo con las necesidades y demandas de las personas.…”
Section: Ediciones Universidad De Salamanca / CC By-nc-ndunclassified
“…Sin embargo, es necesario investigar esta metodología para poderla valorar apropiadamente (García-Iriarte et al, 2017). Mayor consenso existe en la necesidad de que los profesionales de apoyo desarrollen acciones específicas relacionadas con la creación y/o mantenimiento de las redes de relaciones personales, en concreto identificar fuentes de apoyo y diseñar estrategias que permitan a las personas con discapacidad ampliar su red natural de apoyo (García-Iriarte et al, 2016), así como propiciar encuentros que supongan un reconocimiento y valorización de la persona y puedan sentar las bases para otras relaciones más estrechas (Bigby y Wiesel, 2015;Diaz-Garolera et al, 2020). Brophy et al (2015) plantean que se deben desarrollar apoyos creativos e innovadores en coordinación con otros recursos formales e informales de la comunidad, de acuerdo con las necesidades y demandas de las personas.…”
Section: Ediciones Universidad De Salamanca / CC By-nc-ndunclassified
“…In addition, individuals with learning disabilities are more likely to engage in community activities if they have friendship groups (Friedman & Rizzolo, 2018). For the individuals themselves, they describe having friends as important for having someone to discuss their worries with (Garolera et al, 2020). However, people with learning disabilities are more likely to experience social exclusion and loneliness (Wilson et al, 2017), which has a direct negative impact on physical and mental health (Gilmore & Cuskelly, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, individuals with learning disabilities often require support in finding opportunities to meet others so that relationships can develop (Wilson & Frawley, 2016). In one study, most participants reported that they typically seek relationship support from professionals, rather than their family (Garolera et al, 2020). Therefore, professionals should feel equipped to support people with learning disabilities through any relational difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…The social and relational environment in which people are immersed has received growing interest in the literature, due to its relationship with the health, well-being, and social inclusion of people with intellectual disabilities [1,2]. In the case of young people with intellectual disabilities, the literature has shown that these people tend to experience greater difficulties than their non-disabled peers in establishing relationships and that they tend to develop feelings of loneliness [3][4][5][6][7][8][9], their relationships are often limited to family members and professionals, and [10][11][12] they tend to find it difficult to maintain a stable group of friends during this vital stage [13]. In the study of social relationships, three aspects have been distinguished as follows: their existence and quantity, their formal structure, and their functional content, these are termed as social integration, social networks, and relational content, respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…This process brings uncertainty, and new challenges appear in terms of social relationships [26], especially for young people with intellectual disabilities, who tend to experience a longer transition than young people without disabilities [27,28] and experience a progressive reduction in their circles of friendships [7]. During the transition to adult life, it is important to have a social support network made up of peers, since they can play an important role in the quantity and quality of support received [3,4,26].…”
Section: Introductionmentioning
confidence: 99%